Effects of adjustment of transcranial direct current stimulation on motor function of the upper extremity in stroke patients - Lee, Dong-Geol; Lee, Dong-Yeop (Journal of Physical Therapy Science, 2015)
[Purpose] The purpose of this study was to examine the effects of transcranial direct current stimulation (tDCS) applied to the cerebral cortex motor area on the upper extremity functions of hemiplegic patients. [Subjects and Methods] Twenty four Patients with hemiplegia resulting from a stroke were divided into two groups: a tDCS group that received tDCS and physical therapy and a control group that received only physical therapy. A functional evaluation of the two groups was performed, and an electrophysiological evaluation was conducted before and after the experiment. Statistical analyses were performed to verify differences before and after the experiment. All statistical significance levels were set at 0.05. [Results] The results showed that functional evaluation scores for the elbow joint and hand increased after the treatment in both the experimental group and the control group, and the increases were statistically significantly different. [Conclusion] tDCS was effective in improving the upper extremity motor function of stroke patients. Additional research is warranted on the usefulness of tDCS in the rehabilitation of stroke patients in the clinical field.